2018
DOI: 10.1002/ece3.4665
|View full text |Cite
|
Sign up to set email alerts
|

Population genetics and evolutionary history of the wild rice species Oryza rufipogon and O. nivara in Sri Lanka

Abstract: Genetic diversity and population genetic structure of the wild rice species Oryza rufipogon and O. nivara in Sri Lanka were studied using 33 microsatellite markers. A total of 315 individuals of 11 natural populations collected from the wet, intermediate, and dry zones of the country were used in the study. We found a moderate to high level of genetic diversity at the population level, with the polymorphic loci (P) ranging from 60.6% to 100% (average 81.8%) and the expected heterozygosity (H E) varying from 0.… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

3
19
2
1

Year Published

2020
2020
2024
2024

Publication Types

Select...
4
2
2

Relationship

2
6

Authors

Journals

citations
Cited by 11 publications
(25 citation statements)
references
References 57 publications
(118 reference statements)
3
19
2
1
Order By: Relevance
“…low genomic frequency, null alleles, band stuttering and low polymorphisms (Fagerberg et al, 2001;Janderson et al, 2002;Goubert et al, 2016;Wei et al, 2019). Besides these pros and cons, these markers have been used in population genetic studies covering a large spectrum of fauna and fl ora in Sri Lanka (Gunawickrama, 2007;Dammannagoda et al, 2008;De Croos & Pálsson, 2010;Rajkumar et al, 2011;Abeysinghe et al, 2014;Dangalle et al, 2015;Sandamal et al, 2018;Weeraratne et al, 2018). The Ribosomal protein Exon Primed Intron Crossing (Rp EPIC) markers, which have been used to infer genetic variability since 1990's, fl ank the exon regions and detect the polymorphisms across the conserved intron region (Lessa, 1992;Slade et al, 1993).…”
Section: September 2020mentioning
confidence: 99%
“…low genomic frequency, null alleles, band stuttering and low polymorphisms (Fagerberg et al, 2001;Janderson et al, 2002;Goubert et al, 2016;Wei et al, 2019). Besides these pros and cons, these markers have been used in population genetic studies covering a large spectrum of fauna and fl ora in Sri Lanka (Gunawickrama, 2007;Dammannagoda et al, 2008;De Croos & Pálsson, 2010;Rajkumar et al, 2011;Abeysinghe et al, 2014;Dangalle et al, 2015;Sandamal et al, 2018;Weeraratne et al, 2018). The Ribosomal protein Exon Primed Intron Crossing (Rp EPIC) markers, which have been used to infer genetic variability since 1990's, fl ank the exon regions and detect the polymorphisms across the conserved intron region (Lessa, 1992;Slade et al, 1993).…”
Section: September 2020mentioning
confidence: 99%
“…Oryza nivara is the most closely related to O. sativa in terms of phenotypic and lifehistory traits and probably the direct progenitor of Asian rice [32,33]. Both species showed allopatric distribution in Sri Lanka, enhancing the potential of sharing genes with cultivated rice [34][35][36]. The annual O. nivara is globally distributed in the tropics and subtropics of Asia [13] and Southern and Southeast Asia [32,33].…”
Section: Introductionmentioning
confidence: 99%
“…In Sri Lanka, O. nivara was first reported in 1963 in the Trincomalee district of the eastern province [38]. The species is widely distributed but mostly confined to the dry zone and marginally extending to the intermediate zone of the country [34,35,39]. The size, morphology, and geographic distribution of the natural populations of this species vary considerably.…”
Section: Introductionmentioning
confidence: 99%
“…Shishido(2019) evaluated genetic diversity and genetic structure of wild rice populations in seven research sites in Myanmar, and found that these populations retained different levels of genetic diversity. Sandamal (2018) studied 11 natural populations of O. ru pogon and O. nivara from various environmental conditions in Sri Lanka, and found a moderate to high level of genetic structure diversity. Singh (2018) analyzed the genetic diversity of 418 O. ru pogon Griff.…”
Section: Introductionmentioning
confidence: 99%